Enhanced processivity of Dnmt1 by monoubiquitinated histone H3. (3rd December 2019) - Mishima, Yuichi; Brueckner, Laura; Takahashi, Saori; Kawakami, Toru; Otani, Junji; Shinohara, Akira; Takeshita, Kohei; Garvilles, Ronald Garingalao; Watanabe, Mikio; Sakai, Norio; Takeshima, Hideyuki; Nachtegael, Charlotte; et al.
Abstract: DNA methylation controls gene expression, and once established, DNA methylation patterns are faithfully copied during DNA replication by the maintenance DNA methyltransferase Dnmt1. In vivo, Dnmt1 interacts with Uhrf1, which recognizes hemimethylated CpGs. Recently, we reported that Uhrf1‐catalyzed K18‐ and K23‐ubiquitinated histone H3 binds to the N‐terminal region (the replication focus targeting sequence, RFTS) of Dnmt1 to stimulate its methyltransferase activity. However, it is not yet fully understood how ubiquitinated histone H3 stimulates Dnmt1 activity. Here, we show that monoubiquitinated histone H3 stimulates Dnmt1 activity toward DNA with multiple hemimethylated CpGs but not toward DNA with only a single hemimethylated CpG, suggesting an influence of ubiquitination on the processivity of Dnmt1. The Dnmt1 activity stimulated by monoubiquitinated histone H3 was additively enhanced by the Uhrf1 SRA domain, which also binds to RFTS. Thus, Dnmt1 activity is regulated by catalysis (ubiquitination)‐dependent and ‐independent functions of Uhrf1. Abstract : Monoubiquitinated histone H3 stimulates the processivity of Dnmt1. Dnmt1 activity stimulated by monoubiquitinated histone H3 is additively enhanced by the Uhrf1 SRA domain.